The Italian teacher - Rachman, Tom (Viking, 2018)
"A masterful novel that moves from Roman apartments to SoHo galleries to the South of France and tells the story of the son of a great painter striving to create his own legacy, by the bestselling author of THE IMPERFECTIONISTS. Rome, 1955. The artists gather for a picture at a party in an ancient villa. Bear Bavinsky, creator of vast canvases, larger than life, is at the centre of the picture. His wife, Natalie, edges out of the shot. From the side of the room watches little Pinch - their son. At five years old he loves Bear almost as much as he fears him. After Bear abandons their family, Pinch will still worship him, striving to live up to the Bavinsky name; while Natalie, a ceramicist, cannot hope to be more than a forgotten muse. Trying to burn brightly in his father's shadow, Pinch's attempts flicker and die. Yet by the end of a career of twists and compromises, Pinch will enact an unexpected rebellion that will leave forever his mark upon the Bear Bavinsky legacy. A masterful, original examination of love, duty, art and fame, The Italian Teacher cements Tom Rachman as among this generation's most exciting literary voices"--